Narratives of Herbal Medicine Utilisation in the United Kingdom: Scoping Literature Review - Longden-Naufal, Celine; Rolfe, Vivien; Mackonochie, Marion (Frontiers in Pharmacology, 2022)
Using thematic analysis of existing literature, this scoping review aims to explore the narratives of people using herbal medicine (HM) in the United Kingdom. Understanding who is using HM and why will enable better ways of facilitating the use of HM, as well as assist in designing future research. Ethnic groups were found to be primary users of HM in the United Kingdom. A sense of heritage continues to be important for these participants as it allows tradition and culture to stay alive within communities, as well as the ritualistic purposes of these plants. For women, another key demographic, concepts surrounding the naturalness of HMs are associated with the idea of femineity and self-healing. A reoccurring theme in the literature focusing on both ethnic groups and women’s perceptions is the judgement from healthcare practitioners/professionals (HCPs) when addressing the use of HM. However, studies that investigated the perceptions of HCPs on HM confirmed that they often were supportive of using HM where standard treatments had been unsuccessful, and if a patient had anecdotal evidence of a herb having been effective. Delving deeper into public narratives of HM usage will allow conventional healthcare systems to effectively integrate alternative approaches, as well as ensuring that future research into the benefits of HMs is relevant to how people use them.